Artists as Cultural Intermediaries: How Professional Artists Present Their Work on Homepages and Instagram Accounts. - Laukkanen, Henri (Journal of Arts Management, Law & Society, 2025)
This article examines how professional visual artists without gallery representation intermediate their art online. By conceptualizing artists as cultural intermediaries, I studied how their actions affect perceptions of their works in the field of contemporary art. To this end, I conducted media go-along interviews with 18 Finland-based artists and qualitatively analyzed their homepages and Instagram accounts. My findings show that artists shape quality perceptions through, for example, third-party quality signals that reflect their reputations. An important target audience consists of gatekeepers who are vital to artists' careers. The results reveal constraints for creators using the Web to bypass intermediation chains in creative fields.